Optimizing the Use of Social Media as a Means of Promoting MSME Products through the Community Service Program at Bandar Lampung University - Agnesia Br Tarigan (Jurnal Kewirausahaan dan Bisnis, 2026)
The development of social media has provided significant opportunities for Micro, Small, and Medium Enterprises (MSMEs) to market their products more widely and efficiently. However, many MSMEs are still unable to optimally utilize social media as a promotional tool. The community service program implemented by Bandar Lampung University aims to optimize the use of social media as a promotional medium for MSME products. The method used in this activity is a qualitative descriptive approach through outreach, training, and mentoring for MSMEs. The results of the activity show an increase in participants' understanding and skills in using social media, such as Instagram, Facebook, and WhatsApp Business, for promotional purposes. In addition, participants are also able to create more attractive and communicative promotional content, thereby increasing interaction with consumers. The impact of this activity is seen in increased market reach, consumer purchasing interest, and the potential for increased sales of MSME products. Thus, optimizing the use of social media through this community service program has proven effective in supporting the development and competitiveness of MSMEs.